Legal Review of Health Clinic Franchise Business Practices in Indonesia - Fredy Ied Fitriadi; Aryono Aryono; M. Habib (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This thesis, entitled "Legal Review of the Franchise Business Practice of Health Clinics in Indonesia," examines the legal issues arising from the rapid growth of health clinic franchises, particularly breaches of franchise agreements and the legal responsibilities of franchisors and franchisees in healthcare services. The study employs a normative juridical research method using a statutory approach. The primary legal materials include the Indonesian Civil Code, Law Number 17 of 2023 on Health, and Government Regulation Number 35 of 2024 on Franchising. Legal materials are analyzed through juridical interpretation to examine the applicable legal framework. The findings reveal that breaches of franchise agreements in health clinic businesses constitute multidimensional legal violations involving civil, administrative, and health law aspects. Consequently, dispute resolution should not rely solely on the Indonesian Civil Code but must also consider the provisions of Law Number 17 of 2023 on Health and Government Regulation Number 35 of 2024 on Franchising. This integrated approach enhances legal certainty while ensuring a fair balance of rights and obligations between franchisors and franchisees. The study further concludes that existing legislation has not comprehensively regulated the allocation of legal responsibility between franchisors and franchisees, particularly where patient harm results from both deficiencies in the franchise system and operational negligence by the clinic. This regulatory gap may create legal uncertainty in resolving disputes involving health clinic franchises.